Approximation Approach for Timing Jitter Characterization in Circuit Simulators - Gourary, M. M.; Rusakov, S. G.; Ulyanov, S. L.; Zharov, M. M.; Gullapalli, K. K.; Mulvaney, B. J. (Design, Automation, and Test in Europe: Proceedings of the conference on Design, Automation and Test in Europe - Volume 1; 03-07 Mar. 2003, 2003)
A new computational concept of timing jitter is proposed that is suitable for exploitation in circuit simulators. It is based on the approximation of computed noise characteristics. To define jitter value the parameter representation is used. The desired parameters are obtained after noise simulation process in time domain by minimization of integral residual L2 -norm. The approach is illustrated by examples of jitter computation using Spice-like simulator.